Identifikasi Vertebrata Kelas Mamalia di Taman Satwa Taru Jurug Surakarta Sebagai Bahan Materi Pengembangan Video Pembelajaran Biologi SMA Kelas X - Ibnu Fadhlianto (Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
The purpose of this study was to identify Vertebrate animals of the Mammal class, order artiodactyla, family Cervidae in the Jurug Surakarta taru Animal Park, develop interactive video media as a result of identification of vetebrata animals into learning media, know the quality of interactive video media based on assessment by material experts, media experts and biology teachers, and applications in learning. The research method uses an observation method by making direct observations of vertebrate species. The instrument for assessing the quality of interactive video media is based on material aspects and presentation aspects, with a qualitative descriptive analysis design. The results of this study indicate that in Taru Jurug Animal Park Surakarta there are 3 species of animals namely Cervus unicolor, Cervus timorensis, Axis-axis and all three have been identified. Research on the identification of vertebrate animals, especially the mammalian class, order artiodactyla, and the cervidae family can be used for the preparation of interactive video media with material on Biodiversity at the level of genes and species. The quality of interactive video media in terms of material aspects, presentation, and language. Assessment of material experts obtained a percentage of 90.9% so that it was categorized as very valid, media experts obtained a percentage of 88.5% so it was categorized as very valid, biology teacher Veteran 1 Sukoharjo High School obtained a percentage of 92.5% so it was categorized as very valid and biology teacher Nguter 1 Public High School obtained a percentage of 97.5% so it is categorized as very valid. Based on this, it can be concluded that this interactive video media is worthy of being used by teachers as one of the learning media about Biodiversity at the level of genes and species.